Proposed Algorithm MPPT for Photovoltaic System - Bechouat, Mohcene; Sedraoui, ,Moussa; Kahla, Sami (جامعة الوادي - university of el oued, 2018)
A proposed algorithm MPPT (Maximum Power Point Tracking) is proposed in this paper. When the insolation change rapidly, the P&O (Perturb and Observe) algorithm is used to adjust the operating point of the PV (Photovoltaic) array close to the MPP (Maximum Power Point) for fast tracking; also, the INC (Incremental Conductance) algorithm and the fuzzy controller skip drawbacks of the P&O algorithm by decreasing oscillations around the MPP and the underestimated. In addition, to improve the control precision, the effectiveness of proposed algorithm is validated by simulation using Matlab/Simulink, the simulation results show that the proposed algorithm tracks the MPP quickly, reduces the oscillation around the MPP effectively and improves the energy conversion efficiency of the PV panel.
Article
Keywords: MPPT, Photovoltaic, Boost, Simulation